Vodenje odziva na nesrečo v ZDA in Sloveniji - Malešič, Marjan (Teorija in praksa, 2019)
Since the mid 1970s, the USA has developed the Incident Command System (ICS) to improve coordination among the various actors involved in disaster response. The ICS establishes a temporary hierarchical structure, with the Incident Commander (or Unified Command) at the head of the intervention being responsible for co-ordinating and directing activities in the fields of operations, planning, logistics, administration and finances. The ICS is universal and its use is mandatory in all crises, applying to all actors that deal with such crises. The empirical evidence shows the ICS operates relatively well with small or routine disasters, whereas problems grow as the complexity of a disaster increases and ever more actors respond to it, often making improvisation necessary. A comparison of the original American model and the Slovenian practice seen in recent responses to disasters reveals that, functionally, the Slovenian experiences are very close to the American model, whereas the structural similarity is only partial, although analogous solutions in this field were lately developed by the Fire Fighters' Organisation, the Administration for Civil Protection, and individual municipalities.
Keywords: intervencijske službe; modeli vodenja; nesreče; reševanje in pomoč; sistem odzivanja; Slovenija; strukture; varstvo pred naravnimi in drugimi nesrečami; vodenje intervencije; ZDA